2020
DOI: 10.1038/s41598-020-66809-w
|View full text |Cite
|
Sign up to set email alerts
|

Extra Territorial Excursions by European badgers are not limited by age, sex or season

Abstract: european badgers (Meles meles) in medium and high density populations show strong territorial behaviour. territories in these populations are contiguous, well-marked and often unchanging over many years. However, badgers do not always stay within their territorial boundaries. in our mediumdensity population, most individual badgers made extraterritorial excursions (etes) throughout the year. etes were most frequent between April and September and least frequent in December and January (the period of winter let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 66 publications
3
15
0
Order By: Relevance
“…At this density, badgers have been observed to engage in inter-group movements more frequently which is thought to facilitate breeding and foraging 47 . It has therefore been suggested that at lower population densities, increased inter-group movements and reduced competition for resources lessen the motivation for permanent displacement in response to culling 47 , 48 . Another corollary of increased inter-group movement is that vaccination of badgers may be particularly effective in reducing transmission when increased contact between social groups exists, which reduces badger-to-badger bTB transmission 88 and thereby spillover of bTB from badgers to cattle but does not prevent cattle-to-badger transmission.…”
Section: Discussionmentioning
confidence: 99%
“…At this density, badgers have been observed to engage in inter-group movements more frequently which is thought to facilitate breeding and foraging 47 . It has therefore been suggested that at lower population densities, increased inter-group movements and reduced competition for resources lessen the motivation for permanent displacement in response to culling 47 , 48 . Another corollary of increased inter-group movement is that vaccination of badgers may be particularly effective in reducing transmission when increased contact between social groups exists, which reduces badger-to-badger bTB transmission 88 and thereby spillover of bTB from badgers to cattle but does not prevent cattle-to-badger transmission.…”
Section: Discussionmentioning
confidence: 99%
“…60,63 Badger movements are also impacted by their territoriality, avoiding areas occupied by other badger groups, but also displaying occasional extra-territorial movements. 59,61 This suggests a general, but not complete avoidance of areas occupied by other badger groups.…”
Section: Primary Example 231 Ecology and Objectives -Badgermentioning
confidence: 99%
“…We also want to allow the exploratory (state 1) movements to be great enough to occasionally exceed the normal home range or territory. 61 We can draw on statements regarding maximum distance travelled in a night from papers such as, Refs. 58, 60 and 62 to approximate how distance foraging locations could be from a sett, While also confirming the nocturnal activity cycle for the badger.…”
Section: Primary Example 231 Ecology and Objectives -Badgermentioning
confidence: 99%
See 1 more Smart Citation
“…At higher densities t hey are territorial ( Palphramand et al, 2007 ), live in social groups and defend their territories with active fighting, which is effective in spreading tuberculosis between individuals ( Corner et al, 2011 ). Badgers regularly range outside their territories both for mating ( Kelly et al, 2020 ) and while dispersing ( Gaughran et al, 2019 ). In addition, some males hold territories comprising more than one social group ( Gaughran et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%